Hydrothermal Carbonization of Deciduous Woody Biomass: Path to Energy Intensification and Fine Chemicals - SENGOTTIAN, Mothil; VENKATACHALAM, Chitra Devi; RAVICHANDRAN, Sathish Raam; SEKAR, Sarath (Studia Universitatis Babeș-Bolyai Chemia, 2024)
Four deciduous woody feedstocks (Casuarina equisetifolia L., Eucalyptus globulus, Wrightia tinctoria, and Neolamarika cadamba) were subjected to the Hydrothermal Carbonization (HTC) process inside a 50 mL stainless steel hydrothermal reactor at varying temperatures (180°C, 215°C, and 250°C), while keeping water-to-feedstock ratio (6:1 v/w%) and residence time (1.5 h) constant. The mass yield and energy yield of the resulting biomass were calculated as parameters for energy intensification. Characterization of the biomass, biochar, and bio-oil was conducted using elemental analysis, SEM, and GC–MS. Interestingly, the mass yield of biochar decreased with increasing temperature, but it significantly improved the energy densification ratio, with a minimum of 1.06 observed for Neolamarika cadamba biomass at 180°C and a maximum of 1.23 observed for Eucalyptus globulus biomass at 250°C. Moreover, detailed analysis of the bio-oil obtained at 250°C using GC-MS revealed the presence of a diverse range of fine chemicals, including benzyl, carboxylic acid, ester, methyl, phenol, pyrrole, nitro, and aliphatic hydrocarbons. These findings suggest that the HTC process can be optimized to tailor the production of specific value-added chemicals from lignocellulosic woody biomass.